1999
DOI: 10.1161/01.hyp.33.6.1385
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Strength Training Is Associated With Low Arterial Compliance and High Pulse Pressure

Abstract: Abstract-Aerobic exercise training increases arterial compliance and reduces systolic blood pressure, but the effects of muscular strength training on arterial mechanical properties are unknown. We compared blood pressure, whole body arterial compliance, aortic impedance, aortic stiffness (measured by ␤-index and carotid pulse pressure divided by normalized systolic expansion Femoral-dorsalis pedis pulse wave velocity was also higher in the athletes, but carotid-femoral pulse wave velocity was not different. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
160
2
17

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(190 citation statements)
references
References 51 publications
11
160
2
17
Order By: Relevance
“…Similar findings have been seen with increases in stiffness in the central arteries following resistance training in both acute and training studies. 12,41 Miyachi et al 11 reported a 19% decrease in central arterial compliance following 4 months of strength training in 14 young men compared to sedentary controls, but with no changes in peripheral compliance. It should be noted that not all studies have shown an increase in central arterial stiffness following resistance training, 42 but these studies included different populations and employed a different exercise prescription.…”
Section: Aementioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings have been seen with increases in stiffness in the central arteries following resistance training in both acute and training studies. 12,41 Miyachi et al 11 reported a 19% decrease in central arterial compliance following 4 months of strength training in 14 young men compared to sedentary controls, but with no changes in peripheral compliance. It should be noted that not all studies have shown an increase in central arterial stiffness following resistance training, 42 but these studies included different populations and employed a different exercise prescription.…”
Section: Aementioning
confidence: 99%
“…Confounding the recommendation employing RE as an exercise regimen, recent evidence indicates that RE may cause increased arterial stiffness in young, healthy normotensive individuals. 11,12 However, these findings are controversial, as not all studies show an increase in arterial stiffness with resistance training. 13,14 Increases in arterial stiffness, which are associated with increased mortality and morbidity, can lead to decreases in blood flow because of increased peripheral resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Chronic dynamic training is associated with lower central AS in young men 38 and coronary patients, 39 whereas chronic resistance exercise results in stiffer large arteries in both young men 40 and athletes. 41 In the present study we assessed the effects on indices of stiffness (T i , AI) of the large arteries during the acute bouts of exercise (static and dynamic) and during mental stress. Since we did not measure carotid to femoral PWV, our data refer to estimated AS and peripheral wave reflection (by assessing T i and AI as surrogate parameters) rather than directly measured central stiffness per se.…”
Section: Lydakis Et Almentioning
confidence: 99%
“…With respect to exercise, there is evidence that chronic dynamic training has a beneficial effect on AS, 7 whereas chronic resistance exercise may have an unfavourable influence on central haemodynamics. 8,9 Nevertheless, there is little and inconsistent data about the effects of acute bouts of exercise on AS. Acute aerobic exercise was found to induce either an increase 10 or a decrease 11,12 in central AS, whereas studies on acute bouts of resistance exercise showed either an increase 13 or no effect 14 on central AS.…”
Section: Introductionmentioning
confidence: 99%